Palliative endoscopic treatment of malignant central airway obstruction - Mads Bøgh; Sebastian Heinonen; Dalia Gustaityté Larsen; Søren Gade; Sten Schytte; Ulrik Pedersen; Thomas Kjaergaard (BMC Pulmonary Medicine)
Abstract Purpose To examine the outcome of palliative endoscopic treatment of malignant central airway obstruction (CAO) and identify predictors for Days Alive and Out of Hospital (DAOH), overall survival and treatment related complications. Methods Consecutive adult patients treated endoscopically for malignant CAO at Aarhus University Hospital from 2012 to 2022 were included in the study. Statistical analyses were carried out to identify predictors for DAOH, survival and complications. Results 127 consecutive patients met the inclusion criteria. The majority of patients were categorised with stage IV lung cancer, the majority being males, with a median age of 67 years. The endoscopic interventions were mainly tumour debulking combined with airway stent insertion or tumour debulking alone. The complication rate was 21.0% and the mortality rate was 3.9%. In total, 89.8% of the patients experienced symptom relief following surgery, and the majority (92.1%) were discharged from hospital within two days after intervention. Mean survival time following intervention was 144 days, mean DAOH30 was 20.8 and mean DAOH365 was 157. Survival was associated with comorbidity, type of intervention, preoperative respiratory support and postoperative oncologic treatment. A high preoperative ASA-score, preoperative respiratory support, urgency of intervention, female gender and insertion of airway stent were predictors for a poorer DAOH-outcome. Conclusion Endoscopic palliative treatment of malignant CAO is generally feasible and safe, offering symptom relief in most cases. The method is considered an effective measure for short to median term palliation of respiratory distress.